2013
DOI: 10.1016/j.virol.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Translation elongation factor 1B (eEF1B) is an essential host factor for Tobacco mosaic virus infection in plants

Abstract: Identifying host factors provides an important clue to understand virus infection. We selected 10 host factor candidate genes and each gene was silenced in Nicotiana benthamiana (N. benthamiana) to investigate their roles in virus infection. The resulting plants were infected with Tobacco mosaic virus (TMV). The accumulation of viral coat protein and the spread of virus were greatly reduced in the plants that eukaryotic translation elongation factor 1A (eEF1A) or 1B (eEF1B) was silenced. These results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 65 publications
0
39
0
2
Order By: Relevance
“…In some organisms eEF1B also includes a valyl tRNA synthetase. Very little is known specifically about eEF1B from plants other than it has been purified from wheat germ (Lauer et al, 1984) and was shown to play a role in viral replication (Sasvari et al, 2011;Hwang et al, 2013), as have eEF1A (Matsuda et al, 2004;Li and Nagy, 2011) and cap-binding complex subunits (Wang and Krishnaswamy, 2012).…”
Section: Eef1bmentioning
confidence: 99%
“…In some organisms eEF1B also includes a valyl tRNA synthetase. Very little is known specifically about eEF1B from plants other than it has been purified from wheat germ (Lauer et al, 1984) and was shown to play a role in viral replication (Sasvari et al, 2011;Hwang et al, 2013), as have eEF1A (Matsuda et al, 2004;Li and Nagy, 2011) and cap-binding complex subunits (Wang and Krishnaswamy, 2012).…”
Section: Eef1bmentioning
confidence: 99%
“…In Arabidopsis, maltose transporter mutant line (mex1), a typical growth retardation and exceptional chlorotic phenotype, was observed. Those mex1 lines were observed to sustain stress condition raised due to blockage of maltose export, and a GLP (GLP3, At5g20630) was found to be upregulated in those lines (Hwang et al 2013) indicating the involvement of GLPs in those circumstances. A GLP from Citrus limon (ClGLP) was found to show the highest level of expression in mature fruit especially during the transition phase from green to yellow stages of fruit growth (Bruno et al 2014).…”
Section: Glp Expression At Later Stages Of Growthmentioning
confidence: 99%
“…eEF1A also interacts with the 3 UTR of TMV genomic RNA (146) and the ORF6 protein (39). eEF1B, another subunit of eEF1 and the counterpart of E. coli EF-Ts, which is also a subunit of Qβ replicase, interacts with the methyltransferase domain of TMV replication proteins, and knockdown of the eEF1B gene affects TMV multiplication in N. benthamiana leaves (55). Thus, eEF1A and eEF1B are required for efficient viral RNA replication and/or spread in leaves.…”
Section: Host Factors Involved In Tobamovirus Rna Replicationmentioning
confidence: 99%